1928
DOI: 10.1007/bf01954649
|View full text |Cite
|
Sign up to set email alerts
|

Die Lage- und Bewegungsreflexe der Vögel

Abstract: Frfihere Untersuchungen 1 hatten gezeigt, daG am Zustandekommen der kompensatorischen Halss~ellung und an ihrer StSrung nach Labyrinthentfernung die yon den Cristae ausgehenden Erregungen beteiligt sein mfissen. Da diese Befunde der Auffassung der Magnusschen Schule 2 widersprechen, babe ich die Frage untersucht, ob bei den /raglichen Erseheinungen die Maculae i~berhaupt eine RolIe spielen und wit im Experiment die E//elcte der Cristae und Maculae voneinander trennen ~6nnen. I. Versuchanordnung und Beschreibun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1929
1929
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly, reflexes related to cervical and vestibular systems in normal and labyrinthectomized hand-held pigeons led to comparing the flight control system of birds to the autopilot of an airplane. From such studies, Groebbels ( 1926 , 1929 ) proposed that birds control body motion by tracking head motion, essentially “following their turning heads.” In support of this hypothesis, certain wing and tail muscles in the pigeon react to vestibular stimulation, angular visual stimulation, and passive or active lateral head deflections when under simulated flight conditions (Bilo and Bilo, 1978 , 1983 ). Observations of maneuvering pigeons, zebra finches, and lovebirds provide further evidence that head stabilization likely plays a role in flight control (Bilo et al, 1985 ; Davies and Green, 1988 ; Warrick et al, 2002 ; Eckmeier et al, 2008 ; Kress et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reflexes related to cervical and vestibular systems in normal and labyrinthectomized hand-held pigeons led to comparing the flight control system of birds to the autopilot of an airplane. From such studies, Groebbels ( 1926 , 1929 ) proposed that birds control body motion by tracking head motion, essentially “following their turning heads.” In support of this hypothesis, certain wing and tail muscles in the pigeon react to vestibular stimulation, angular visual stimulation, and passive or active lateral head deflections when under simulated flight conditions (Bilo and Bilo, 1978 , 1983 ). Observations of maneuvering pigeons, zebra finches, and lovebirds provide further evidence that head stabilization likely plays a role in flight control (Bilo et al, 1985 ; Davies and Green, 1988 ; Warrick et al, 2002 ; Eckmeier et al, 2008 ; Kress et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…From Bechterew's results we should then have to conclude also that the slow phase cannot be of vestibular origin. So far as I can see, the conclusion to be drawn from his results should be that in that type of nystagmus both phases, the quick and the slow, are of central origin, produced by unbalanced activities of the central neural mechanisms, just as is any nystagmus which is elicited by some means in an animal which is bilaterally labyrinthectomized [lesion of the vestibular nuclei in the brain-stem (Spiegel and Sato, 1926) or galvanization of the head (Groebbels, 1922)]. The main objection to Maupetit's thesis is the fact that on habitual rotation the quick phase disappears gradually, whereas the slow phase, expressing itself then as a slow deviation, remains (Dodge,192U).…”
Section: Labyrinthine Acceleratory Reflexes a Reflexes Upon Angular A...mentioning
confidence: 96%
“…Breuer (1874) showed that this is true also if visual stimuli are excluded. Later observations were made by Trendelenburg (1906a, 19064), Trendelenburg and Kiihn (1908), Huxley (1913), andGroebbels (1922).…”
Section: Labyrinthine Positional Reflexesmentioning
confidence: 99%
“…Davis and Pollock (11) have used the method of decerebration to study the tone of neck and limb muscles under various types of intra-oral destruction of the labyrinth on one and on both sides. Groebbels (40), in particular, has made elaborate studies of posture and tonus in pigeons under various types of labyrinthine stimulation. He has succeeded in gaining objective measures of changes in tonus and has described these changes as they stand related to each of the three ampullae.…”
Section: Vmentioning
confidence: 99%